Efficacy of Transcranial Direct-Current Stimulation in Women With Provoked Vestibulodynia. Issue 8 (August 2017) - Morin, Annie; Leonard, Guillaume; Gougeon, Véronique; Cyr, Marie-Pierre; Waddell, Guy; Bureau, Yves-André; Girard, Isabelle; Morin, Mélanie
Abstract : (Abstracted from Am J Obstet Gynecol 2017;216(6):584.e1–584.e11) The most frequent cause of premenopausal dyspareunia is provoked vestibulodynia (PVD). Patients with PVD have acute recurrent pain at the vaginal entrance in response to attempted vaginal penetration or application of pressure.